A literature review of factors influencing breast cancer screening in Asian countries - Ahmadian, Maryam; Abu Samah, Asnarulkhadi (Marsland Press, 2012)
Breast cancer is a major public health concern among Asian women. As breast cancer is often diagnosed in advanced stages in younger women, mortality rates are frequently higher compared with rates in developed nations. Due to the influence of various psychological, social, and cultural factors on breast cancer, women are reluctant to screen their breast cancer symptoms at the early stages when treatment is most expected to be successful. Screening options for Asian women are also limited because of demographic constrains and their knowledge of preventive health measures. This paper proceeds to review the existing literature on factors influencing breast cancer screening among Asian women. For the most part, health care professionals, medical doctors, gynecologists, and breast cancer advocates should find actual ways to overcome psychological barriers such as beliefs about pain, fear, embarrassment, and modesty of women through public awareness campaigns. Considerable attention should be also devoted to lower socioeconomic status women. In the same way, health care providers should explain to the women about the importance of breast cancer as a common disease and the existence of breast cancer screening programs in a small scale approach, as well as the benefits that participation in these programs can offer. This initiative is about enhancing health status among women and it is part of community development endeavor.